Integrating the social support theory and technology acceptance model of social commerce websites - Syed Shah Alam; Nurkhalida Makmor; Mohammad Masukujjaman; Zafir Khan Mohamed Makhbul; Mohd Helmi Ali; Abdullah Al Mamun (Revista Galega de Economía, 2023)
The expansion of social commerce websites has gradually transformed people’s life in terms of social interaction during leisure time spending. Communication has been simplified because of the advancement of information communication technology. Information sources will help consumers to determine and find information sources easily. Nevertheless, consumers face the possibility of encountering a big challenge in understanding the contents as the information may lead to untruthfulness and biases. By combining the technology acceptance model (TAM) and social support theory (SST), the current research developed a detailed purchase intention model to analyse relationships connected with social commerce websites. Trust was tested as the mediating effect on social commerce websites. The study was undertaken using the quantitative approach, while non-probability (convenience sampling) was employed by online survey. A total of 392 respondents participated in this study. This method demonstrates that different forms of social support (emotional and informational) have a strong relationship with TAM, trust, and purchase intention. Nonetheless, perceived usefulness and purchase intention revealed insignificant relationships. Moreover, trust was a mediator between social supports and TAM constructs in the social commerce purchase intention model. Based on the analysed samples, the proposed model appears to fit and explicitly explains each relationship. Therefore, the integration and extension of constructs may serve as new potential research directions. Furthermore, the findings have considerable potential to be employed when marketers and practitioners develop social commerce websites.